CMTD Project Information Integration System - Babilonia, Lennon G. (Quezon City University of the Philippines Diliman, 2008)
To build a foundation for a sound and swift decision-making in managing projects it is important to build an information management system that will support the implementation of projects under the AFP Modernization Program. The AFP Modernization Program has five major components. The most significant of the five components is the Capability, Material and Technology Development (CMTD) which involves acquisition of defense technologies. The AFP Modernization Program Management Office or AFPMPMO is the office directly responsible in managing the CMTD Projects. In monitoring the progress of projects, the AFP MPMO utilizes its divisions to collect information, generate reports, and provide updates to higher leadership for decision making. The CMTD Project Information Integration Project is a system of collecting, sharing, and monitoring information about CMTD Projects. The system involves capturing of important information about CMTD Projects in all its stages by the divisions that are monitoring them. It aims to come out with a common set of information that can readily be used by the divisions of the Office, particularly its staff and personnel who are directly involved in monitoring and facilitating the progress of CMTD Projects.
The system will provide a venue for integrating all the information from all the stages in the implementation of the CMTD projects. Specifically, it has the following features; capture of important information from all stages and from all the possible sources, collection of information by one division, from the different divisions, that will manage them, internal sharing of information between divisions, staffs and personnel of the office, and storage of information. With this system, the availability of vital information for generating reports, updating stakeholders and for decision making by higher leadership will be easily accessible. Likewise, having common information available for all the divisions and staffs will ensure consistency and widespread understanding of what the projects are all about and their current status. Further, with the AFP policy of rotating personnel from one office to another, it is but necessary to establish an information database that can be handled down from generation to generation. The system, which is basically a knowledge management tool, will also provide the necessary foundation for the establishment of project database which will be pursued in the future by the AFP MPMO.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: CMTD Project; Information Integration System; Project management; Knowledge management